Energy balance monitoring in tennis players - Marks, B. L.; Galleher, E.; Moore, T.; Katz, L. M. (Medicine and Science in Tennis, 2003)
Thus the purpose of this study was to compare energy balance for a typical week of activity, including energy intake and energy expenditure via self reports vs. Caltrac activity recordings in male college tennis players.